Youth suicide and bullying challenges and strategies for prevention and intervention - Goldblum, Peter; Espelage, Dorothy L.; Chu, Joyce; Bongar, Bruce (Oxford, UK Oxford University Press, 2015)
Youth Suicide and Bullying presents an authoritative review of the science demonstrating the links between these two major public health concerns alongside informed discussion and evidence-based recommendations. The volume provides sound, scientifically grounded, and effective advice about bullying and suicide at every level: national, state, and community. Chapters provide details on models of interpersonal aggression; groups at risk for both bullying and suicide (such as sexual minorities); the role of stigma; family, school, and community-based youth bullying and suicide prevention programs, and more. Each chapter concludes with recommendations for mental health providers, educators, and policymakers. Compiling knowledge from the most informed experts and providing authoritative research-based information, this volume supports efforts to better understand and thereby reduce the prevalence of victimization and suicide.
Part I. Overview: state of the science and current challenges -- Part II. Defining the problem: prevalence, predictors, and protectors -- Part III. Cultural perspectives -- Part IV. Explanatory models -- Part V. Educational approaches -- Part VI. Public health approaches -- Part VII. Conclusions and future directions.
Includes bibliographical references and index.
Keywords: Bullying; Bullying in schools; Youth -- Suicidal behavior; Suicide -- Prevention